2018
DOI: 10.1159/000487102
|View full text |Cite
|
Sign up to set email alerts
|

The Neonatal Microbiome and Its Partial Role in Mediating the Association between Birth by Cesarean Section and Adverse Pediatric Outcomes

Abstract: Background: Cesarean sections (CS) are among the most commonly performed surgical procedures in the world. Epidemiologic data has associated delivery by CS with an increased risk of certain adverse health outcomes in children, such as asthma and obesity. Objective: To explore what is known about the effect of mode of delivery on the development of the infant microbiome and discuss the potentially mediating role of CS-related microbial dysbiosis in the development of adverse pediatric health outcomes. Recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 98 publications
1
53
0
2
Order By: Relevance
“…The stable phase started from the 31st month of life with clusters 8‐10 becoming most dominant . Several factors were reported to perturb gut homeostasis by affecting the composition of gut microbiome, including cesarean section (C‐section), antibiotic use, dietary ingredients, hygiene standards, and geographical distribution . The contribution of each factor to changes in the gut microbiome with reference to its link to T1D is discussed below.…”
Section: The Gut Barriermentioning
confidence: 99%
“…The stable phase started from the 31st month of life with clusters 8‐10 becoming most dominant . Several factors were reported to perturb gut homeostasis by affecting the composition of gut microbiome, including cesarean section (C‐section), antibiotic use, dietary ingredients, hygiene standards, and geographical distribution . The contribution of each factor to changes in the gut microbiome with reference to its link to T1D is discussed below.…”
Section: The Gut Barriermentioning
confidence: 99%
“…Early exposure to microbes in utero may prepare the infant's immune system for the challenges of the external environment . While many studies have extensively described the gut microbiome in infants and its relationship to health outcomes, the infant skin microbiome is less well‐characterized. Here, we highlight four recent studies that used 16S rRNA gene sequencing or ITS2 sequencing to understand the impact of delivery mode on initial skin colonization …”
Section: Establishment Of the Skin Microbiomementioning
confidence: 99%
“…Cesarean delivery has the potential to interrupt the normal hierarchy of skin microbe colonization achieved during labor and vaginal delivery. Delayed acquisition of the normal gut microbiome, or disruption through use of antibiotics or colonization with potential pathogens, can have a profound impact on infant health, both in the short‐term and long‐term . Cesarean section increases colonization of the gut by Staphylococcus and Clostridium (opportunistic genera) and increases the likelihood of developing diseases including, atopic dermatitis, asthma, and obesity .…”
Section: Establishment Of the Skin Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the gut microbiome of vaginally delivered infants more closely resembles their mothers' vaginal microbiome and thus more commonly consists of potentially beneficial microbiota such as Lactobacillus, Bifidobacterium and Bacteroides. Conversely, the microbiome of infants born via C-section shows an increased prevalence of either skin flora or potentially pathogenic microbial communities such as Klebsiella, Enterococcus and Clostridium [13]. …”
Section: Introductionmentioning
confidence: 99%